Perancangan Jaringan Sensor Nirkabel (JSN) untuk Memantau Suhu dan Kelembaban Menggunakan nRF24L01 - Dwi Intan Af'idah; Adian Fatchur Rochim; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2014)
The environmental condition in a large areas often requires the monitoring. For example, in the case of greenhouse were used to cultivation experiments, fertilization experiments, plant resistance experiments, tissue culture experiments, experimental planting of crops in the off-season, and it needs equipment to monitor and control the environmental conditions to suit the characteristics required environment. The extent of land that is must be monitored, making it needs distribute the monitor at some point so that monitoring of environmental conditions can cover the entire desired area. This is the basis for the design of wireless sensor network for monitoring temperature and humidity using the communication module nRF24L01 +. The system consists of hardware for measuring the temperature and humidity at some point in a certain area. The system is divided into several sections that is referred to as nodes. Node in the system is divided into two functions, namely the sensor node and the concentrator node.. There are two the sensor nodes which will serve to data of temperature and humidity in separate areas and transmit data to the concentrator node. The communication between nodes is done using a module nRF24L01+. The design of communication protocol designed to connect between nodes concentrator with a sensor node capable of running properly. This makes the system capable of monitoring temperature and humidity through a web page, so it can be known conditions of temperature and humidity at some point at the maximum range of 93 meters.